THE POSITION AND RIGHTS OF WOMEN IN POLITICAL PARTIES IN INDONESIA (CASE STUDY: PARTAI KEBANGKITAN BANGSA OF NORTH SUMATRA): Posisi dan Hak Perempuan dalam Berpartai Politik di Indonesia (Studi Kasus: Partai Kebangkitan Bangsa Sumatera Utara) - Zuldi Yariza Magribi Matondang; Aprilinda M. Harahap (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Women's involvement in Indonesian politics is an essential part of fulfilling constitutional rights and strengthening inclusive democracy. Although the 30% quota policy for women's representation has been stipulated in election regulations, its implementation at the political party level has not been fully optimal, including in the National Awakening Party (PKB) of North Sumatra. This study aims to analyze the position, rights, and opportunities of women within the structure and leadership of PKB North Sumatra and to identify supporting and inhibiting factors for women's political involvement. The study used a qualitative method with a descriptive-analytical case study approach through in-depth interviews with PKB North. Sumatra female administrators and cadres as primary data, and supported by party documents, regulations, and scientific literature as secondary data. The results show that PKB North Sumatra normatively and structurally does not apply gender discrimination, because women and men have equal rights to vote, be elected, express opinions, and hold strategic positions based on the principles of suitability and capacity. However, quantitatively, women's representation in PKB North Sumatra's legislative body is still relatively low and has not reached the ideal quota, which is influenced by cultural, structural, and electoral dynamics barriers, rather than internal party restrictions. Nevertheless, the North Sumatra National Awakening Party (PKB) has made efforts to empower women through its Women's National wing, political education, and strengthening women's cadre development. This research confirms that women's political involvement in the North Sumatra PKB has moved beyond mere administrative fulfillment to more substantive participation, although ongoing strengthening is still needed to optimize women's representation in the political process and public policy.